English Pedagogy for Student with Emotional and Behavioral Disorders In An Inclusive School - Laela Hikmah Nurbatra; Desty Meidina Andhini (Jurnal Perempuan dan Anak, 2021)
Inclusive school is a public school that the student with special needs can be educated together with normal students. Expanding the potential that they have through the appropriate teaching strategies is crucial to implement, especially for the student with EBD. The student with EBD is a student that has aggressive behavior and substantial negative influence in the learning process. In accordance to that, the researcher wants to investigate (1) the teaching strategies used by the English teacher for the student with Emotional and Behavioral Disorders (EBD), (2) the implementation of teaching strategies used by the English teacher for the student with Emotional and Behavioral Disorders (EBD). Using qualitative method, the research involves one English teacher of SD Satu Atap Sumbersari 1 Malang Inclusive School. The instruments used were observation and interview. The current research revealed that there were three strategies used by the English teacher at SD Satu Atap Sumbersari 1 Malang Inclusive School. First, the teacher shows the interest towards students’ progress through communication to the student with EBD. Second, giving the student an understanding to have control for everything occurring in their life by giving the student with EBD punishment when break the rules. Third, conducting class activities relevant to students’ interest with alternative activities made by the English teacher.